2011
DOI: 10.1002/em.20661
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive exposure to zinc oxide nanoparticles induces dna damage in human nasal mucosa mini organ cultures

Abstract: Data on the toxicological properties of zinc oxide nanoparticles (ZnO-NPs) is incomplete. ZnO-NPs may enter humans via inhalation or ingestion. The aim of the current study was to evaluate ZnO-NP-induced genotoxicity in three-dimensional (3D) mini organ cultures (MOCs) of human nasal mucosa following repeated exposure to ZnO-NP and regeneration. Nasal MOCs of 10 patients and ZnO-NPs were cultivated for one week and then characterized by electron microscopy. Nasal MOCs were partially covered by ciliated epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 34 publications
4
34
1
Order By: Relevance
“…exposed 3D mini-organ cultures of human nasal mucosa on three subsequent days to ZnONP for 1h and did not find any acute toxicity or apoptosis but did observe DNA damage 218 . Thus, 3D models can be applied to assess cumulative effects while this is hampered in 2D cultures as cells do not survive longer cultivation periods, dedifferentiate or rapidly divide causing dilution of the NP and an associated dilution of any possible effects.…”
Section: Effect Of a 3d Environment On Np Toxicitymentioning
confidence: 90%
“…exposed 3D mini-organ cultures of human nasal mucosa on three subsequent days to ZnONP for 1h and did not find any acute toxicity or apoptosis but did observe DNA damage 218 . Thus, 3D models can be applied to assess cumulative effects while this is hampered in 2D cultures as cells do not survive longer cultivation periods, dedifferentiate or rapidly divide causing dilution of the NP and an associated dilution of any possible effects.…”
Section: Effect Of a 3d Environment On Np Toxicitymentioning
confidence: 90%
“…64 Repetitive exposure to 76 × 53 nm ZnO NPs (5 µg/mL) of human nasal mucosa mini-organ cultures induced DNA damage, established using the comet assay. 65 This damage was further increased after a 24-hour regeneration period. The NPs were distributed in the cytoplasm and the nucleus.…”
Section: Genotoxicity Studies In Vivo and In Vitro In Vivo Studiesmentioning
confidence: 96%
“…Recent studies have shown that ZnO nanoparticles induced DNA damage in different cell lines, e.g. epidermal, nasal mucosa, lymphoblastoid, liver, kidney and neuronal cells (Bhattacharya et al, 2014;Guan et al, 2012;Hackenberg et al, 2011;Sharma et al, 2011Sharma et al, , 2012Valdiglesias et al, 2013). Yet, a complete understanding of the cell toxicity mechanism is still to be achieved.…”
Section: Introductionmentioning
confidence: 99%